2015
DOI: 10.1162/jocn_a_00739
|View full text |Cite
|
Sign up to set email alerts
|

The Strength of Gradually Accruing Probabilistic Evidence Modulates Brain Activity during a Categorical Decision

Abstract: The evolution of neural activity during a perceptual decision is well characterized by the evidence parameter in sequential sampling models. However, it is not known whether accumulating signals in human neuroimaging are related to the integration of evidence. Our aim was to determine whether activity accumulates in a non-perceptual task by identifying brain regions tracking the strength of probabilistic evidence. Functional magnetic resonance imaging was used to measure whole-brain activity as choices were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…A potential problem with these previous studies of delaying decisions by gradually revealing a stimulus is that manipulating stimulus evidence is likely to affect a different level of cognitive processing (O'Connell, Dockree, & Kelly, 2012) while confounding perceptual detection with evidence accumulation. Thus, this type of manipulation may not selectively identify the neural integration process (Wheeler et al, 2015). Nevertheless, our observation of accumulator-like activity in the bilateral anterior insula is consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A potential problem with these previous studies of delaying decisions by gradually revealing a stimulus is that manipulating stimulus evidence is likely to affect a different level of cognitive processing (O'Connell, Dockree, & Kelly, 2012) while confounding perceptual detection with evidence accumulation. Thus, this type of manipulation may not selectively identify the neural integration process (Wheeler et al, 2015). Nevertheless, our observation of accumulator-like activity in the bilateral anterior insula is consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…This approach may suffice in controlling for the perception/accumulation confound, though it precludes the use of simple, continuous stimuli. Tremel and Wheeler (2015) maintained a constant input of degraded images in a face/house recognition task, but RTs were not sufficiently long (around 3 seconds) to measure ramping activity. Also, it is possible that face or object recognition is a nonlinear process and that revealing degraded images or masked local parts would interact with the accumulation process in a temporally unstable way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we focus on the vmPFC and an additional area, the intraparietal sulcus (IPS)/inferior parietal (IP), both of which are associated with both reward and concept representation. IPS/IP is active during categorization and is sensitive to category representation in humans (Seger et al, 2015;Wheeler et al, 2015) and nonhuman primates (Sarma et al, 2016). Braunlich and Seger (2016;K.…”
Section: Integration Of Reward and Concept Representations In Categormentioning
confidence: 99%
“…Work with patients showed that performance on the weather prediction task is primarily dependent on the basal ganglia, and not as much on medial temporal lobe learning system [Knowlton et al, 1994, Knowlton et al, 1996. Later neuroimaging work confirmed the contribution of the basal ganglia to probabilistic category learning [Shohamy et al, 2004, Poldrack et al, 2001, Ashby and Maddox, 2005, Shohamy et al, 2008, Wheeler et al, 2015, Soltani et al, 2016. The computational framework of reinforcement learning (RL) has been instrumental in explaining the involvement of the basal ganglia in trial-and-error learning: by learning the future reward value of observations (or states) using prediction errors that are conveyed by midbrain dopaminergic neurons , Montague et al, 1996, Niv, 2009, Schultz et al, 1997.…”
Section: Probabilistic Categorization Taskmentioning
confidence: 99%